Screening method of cellulose-producing fungi based on chromogenic enzyme reaction - MA Xuekun; XIE Yanping; WANG Juan; LIU Gang (Shenzhen Daxue xuebao. Ligong ban)
Congo red staining and Gram iodine staining methods are common methods for screening of cellulase-producing fungi, but there are shortcomings such as insufficient color development and being easy to be interfered by medium components. The establishment of a convenient and sensitive screening method is helpful for rapid and accurate screening of cellulase-producing fungi. Firstly, oligosaccharide concentration and cellulase activity were analyzed through the gluco-oligosaccharide oxidase-based horseradish peroxidase colorimetric method. The results showed that within a certain concentration, optical density value was linearly correlated with the oligosaccharide concentration and cellulase activity. Then, soil and woody samples were taken from the forest land of Tanglang Mountain in Shenzhen city, Guangdong province of China, diluted to proper concentration and coated on modified Martin's medium agar plates. After the purification of fungi, the single colonies were picked and inoculated in 24 well plates containing modified Martin's medium and cultivated for 72 hours. After centrifugation, the culture supernatant was added to the oligosaccharide oxidase based horseradish peroxidase colorimetric system for color development, and the cellulase producing strains were screened according to the color depth. Finally, the strains obtained in primary screening were rescreened with a cellulase-producing medium, and 15 fungal strains with relatively higher cellulase producing productivity were obtained and preliminarily identified. This work provides an easy and efficient method for screening cellulase-producing fungi.